Anaerobic single‐cell dispensing facilitates the cultivation of human gut bacteria. (1st March 2022) - Afrizal, Afrizal; Hitch, Thomas C. A.; Viehof, Alina; Treichel, Nicole; Riedel, Thomas; Abt, Birte; Buhl, Eva M.; Kohlheyer, Dietrich; Overmann, Jörg; Clavel, Thomas
Summary: Cultivation via classical agar plate (CAP) approaches is widely used to study microbial communities, but they are time‐consuming. An alternative approach is the application of single‐cell dispensing (SCD), which allows high‐throughput, label‐free sorting of microscopic particles. We aimed to develop a new anaerobic SCD workflow to cultivate human gut bacteria and compared it with CAP using faecal communities on three rich culture media. We found that the SCD approach significantly decreased the experimental time to obtain pure cultures from 17 ± 4 to 5 ± 0 days, while the isolate diversity and relative abundance coverage were comparable for both approaches. We further tested the total captured fraction by sequencing the sorted bacteria directly after growth as bulk biomass from 2400 dispensed single cells without downstream identification of individual strains. In this approach, the cultured fraction increased from 35.2% to 52.2% for SCD, highlighting the potential for deeper cultivation projects from single samples. SCD‐based cultivation also captured species not detected by sequencing (16 ± 5 per sample, including seven novel taxa). From this work, 82 human gut bacterial species across five phyla (Actinobacteriota, Bacteroidota, Desulfobacterota, Firmicutes and Proteobacteria) and 24 families were obtained, including the first cultured member of 11 novel genera and 10 novel species that were fully characterized taxonomically.